Multikulturalisme di Indonesia Menurut Al-Qur’an - Yasin, Nur (Universitas Nurul Jadid, 2019)
Abstract: Multiculturalism is a form of cultural diversity in Indonesia. This variety has been established for a long time before the existence of the Indonesian state, still in the form of an archipelago. The diversity turns out to be fertile until now, because it is based on the spirit of the Qur'an. It's just that this symbol still needs to be fought continuously because there are always problems and imperfect shapes. So that at one time really manifested the Qur'anic multiculturalism. Keywords: Multiculturalism, Culture, and Indonesian